2013
DOI: 10.1128/aac.01271-12
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Vancomycin-Resistant Enterococcus faecalis: a Case-Case-Control Study

Abstract: e Although much is known about vancomycin-resistant (VR) Enterococcus faecium, little is known about the epidemiology of VR Enterococcus faecalis. The predilection of VR E. faecalis to transfer the vancomycin resistance determinant to Staphylococcus aureus is much greater than that of VR E. faecium. The epidemiology of VR E. faecalis has important implications regarding the emergence of vancomycin-resistant S. aureus (VRSA); 8 of 13 reported VRSA cases have been from Michigan. A retrospective case-case-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 23 publications
2
35
0
5
Order By: Relevance
“…Morris et al showed that the use of multiple antibiotics could be a risk factor for emerging VRE (43). A definite conclusion from these previous reports and from our data is that antimicrobial stewardship should be required to prevent emerging VRE, as mentioned in a recent case-control study (44).…”
Section: Discussionsupporting
confidence: 76%
“…Morris et al showed that the use of multiple antibiotics could be a risk factor for emerging VRE (43). A definite conclusion from these previous reports and from our data is that antimicrobial stewardship should be required to prevent emerging VRE, as mentioned in a recent case-control study (44).…”
Section: Discussionsupporting
confidence: 76%
“…Eighteen studies were eligible for inclusion including: 5 multicenter studies reporting the incidence of VRE infections [2,[13][14][15][16] and 13 studies (4 multicenter and 9 single center) evaluating relevant outcomes [17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with uninfected patients, patients with VR E. faecalis infections had a 2.8-fold increased risk (11.4% vs 33.9%) [18] of being discharged to a LTCF and patients with CO VR E.…”
Section: Discharge To a Ltcfmentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies demonstrated that long hospitalization periods cause increased risk of colonization, higher rates of morbidity and mortality and cost [21][22][23][24] . In a study by Pan et al, long stay in the intensive care unit was found as a major risk factor for VRE colonization 22 .…”
Section: Discussionmentioning
confidence: 99%